PENGARUH PEMBERIAN AROMA TERAPI MINYAK JAHE TERHADAP PENURUNAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Windriyani, Zela; Savita, Riza; Patimah, Siti (JURNAL SMART ANKes, 2025)
Emesis gravidarum is a common complaint experienced by pregnant women in the first trimester, characterized by nausea and vomiting that can disrupt daily activities and risk reducing nutritional intake. According to data from the Melintang Community Health Center (Puskesmas), there has been a significant increase in cases of emesis gravidarum from year to year, reaching 123 cases in the first trimester of 2025. The purpose of this study was to determine the effect of ginger oil aromatherapy on reducing emesis gravidarum in pregnant women in the first trimester. This study used a pre-experimental design with a one-group pretest-posttest approach. A sample of 95 pregnant women in the first trimester experiencing emesis gravidarum was selected using a purposive sampling technique. The intervention, which included ginger oil aromatherapy, was administered for four consecutive days every morning. Emesis levels were measured using the PUQE-24 questionnaire before and after the intervention. The results of the paired sample t-test showed a significant difference between the pretest and posttest scores, with a p-value <0.05. It can be concluded that ginger oil aromatherapy is effective in reducing the frequency and intensity of emesis gravidarum. This study recommends ginger oil aromatherapy as a safe and easy-to-implement complementary therapy for pregnant women with mild to moderate nausea and vomiting in the first trimester. Keywords: Aromatherapy, Ginger Oil, Emesis Gravidarum, Pregnant Women